Critical Review of Fintech Management: Critical Review of Fintech Management - Dheasey Amboningtyas; Adji Seputro; Adhi Anjar Wicaksono (Institute of Computer Science (IOCS), 2020)
The purpose of this study is to determine the recognition, measurement, and disclosure in accordance with the implementation of management in Fintech, which is critically reviewed effectively and efficiently from the perspective of Critical Management Studies (CMS). Data collection is done by interviewing techniques and other secondary data support. Respondents in this study were the Financial Services Authority (OJK), the general public (30 respondents). This study used two stages of discussion, namely, using the variables of Good Corporate Governance (GCG) and through a Critical Management Studies (CMS) perspective. Data analysis method uses a critical paradigm by testing the validity of data based on data trigulation and theory. The results of the study found that the implementation of the policy from the regulator (OJK) was not fully maximized, there were still information gaps between the service users and Fintech members. Fintech management is deemed unable to be fully implemented.